The Enactivist Dimension of the Book “Captivity” by Valeria “Nava” Subotina - Shteinbuk, Feliks; Gordiienko, Yulia (Respectus Philologicus, 2026)
The lack of temporal distance from the works of contemporary Ukrainian literature, devoted to themes of the Russian-Ukrainian war, necessitates the search for adequate methods for the effective analysis of non-fiction literary works. The purpose of the article is to propose an algorithm to interpret texts like V. Subotina’s book Captivity. The hermeneutic method and an enactivist approach were used to achieve the goal. The algorithm for analysing Subotina’s book considers such corporal correlates as pain, hunger, and touch since the core phenomenon of the enactivist approach is the body. The conclusion is that the corporal correlates of pain, hunger, and touch can become not only a means of suffering and unfair deprivation of personal freedom, but, paradoxically, a source of inspiration to live, fight, and create. In the proposed context, the enactivist approach shows its potential in view of the functional use of relevant corporal correlates and can be applied in further studies of various genres of non-fiction literary samples.
Keywords: Valeria Subotina; Russian-Ukrainian war; non-fiction literature; enactivist approach; corporal correlate